Detection of adeB and basD Genes in Lung Tissue Samples of Rattus Norvegicus Injected with Acinetobacter Baumannii - Augy Sausan Jannati Damartiya; Desi Nur Hasanah; Fitria Diniah Janah Sayekti (Indonesian Journal of Global Health Research, 2026)
Acinetobacter baumannii is an opportunistic pathogen and a major cause of nosocomial infections, characterized by high resistance to multiple antibiotics. The success of its colonization and virulence is influenced by resistance factors such as the adeB gene and nutrient acquisition factors such as the basD gene. This study aimed to detect the presence of adeB and basD genes in lung tissue of Rattus norvegicus intravenously injected with clinical isolates of Acinetobacter baumannii. Six healthy female rats were divided into treatment groups with observation periods of 10 hours and 18 hours post-infection. Lung tissues were collected for DNA extraction, followed by PCR amplification using specific primers for adeB (549 bp) and basD (533 bp). Gel electrophoresis results showed that both genes were clearly detected in the bacterial isolate positive control, but not in lung tissue samples post-infection. The failure of detection in tissue samples is likely influenced by the low bacterial load, host-dependent regulation of gene expression, and the presence of PCR inhibitors derived from lung tissue. These findings indicate that although adeB and basD play crucial roles in resistance and virulence, their presence in host tissues is not always detectable by conventional PCR. Therefore, more sensitive detection methods are required for molecular analysis in in vivo models.